The gender achievement gap in grades and standardised tests—what accounts for gender inequality? - Lehti, Hannu; Laaninen, Markus (Frontiers Media SA, 2025)
We studied the gender achievement gap in grades and standardised test scores in Finland, where the gender differences are largest among OECD countries. We compared the gender achievement gap in standardised test scores from PISA surveys and grades from high-quality school registers in literacy. Furthermore, we analysed how grades differ from standardised test scores by family background and students’ SES composition of the schools. By using the Blinder-Oaxaca decomposition method, we explored how different characteristics between girls and boys explain gender differences in grading. Our findings indicate that boys’ grades were lower than can be expected based on standardised test scores. The gender gap in grades was explained by boys’ lower reading interests, effort put into schoolwork, and conscientiousness on homework. However, even adjusting for schooling characteristics and competence, boys have lower grades than test scores in schools that have low SES student composition.